Multiple Cause of Death, 1997 ([Verlag nicht ermittelbar], 2001)
This data collection includes information about the cause of all recorded deaths occurring in the United States, Puerto Rico, the Virgin Islands, Guam, and American Samoa during 1997. Data are provided concerning underlying causes of death, multiple conditions that caused the death, place of death, residence of the deceased (e.g., region, division, state, county), whether an autopsy was performed, and the month and day of the week of the death. In addition, data are supplied on the sex, race, age, marital status, education, usual occupation, and origin or descent of the deceased. Mortality Detail data for 1997 also can be extracted from this file. The Mortality Detail records are contained in the first 159 positions of these Multiple Cause records. The multiple cause of death fields were coded from the MANUAL OF THE INTERNATIONAL STATISTICAL CLASSIFICATION OF DISEASES, INJURIES, AND CAUSE-OF-DEATH, NINTH REVISION (ICD-9), VOLUMES 1 AND 2.